An overview of and a proposed reform for the organ procurement: System of the United States - RYAN, Spencer (Journal of Economics Library, 2025)
Over 107,000 Americans are currently awaiting a lifesaving organ transplant. The vast shortage of organs for transplant in the United States is commonly known, but few are aware that the capacity exists for an additional 28,000 organs to be procured each year. These viable organs are not procured because of the limitations of the market and governance structure of the organizations primarily responsible for organ procurement across the United States, Organ Procurement Organizations (OPOs). In this paper, the author provides an overview of the current organ procurement system and its flaws, debates the newly revised organ procurement regulations to come into effect in 2022, and offers a sweeping, market-based reform proposal for the organ procurement system. Keywords. Organ procurement, Organ procurement organizations (OPOs). JEL. I10, I11, I18.